Phase I dose escalation study of lestaurtinib in patients with myelofibrosis. Issue 9 (2nd September 2015) - Hexner, Elizabeth O.; Mascarenhas, John; Prchal, Josef; Roboz, Gail J.; Baer, Maria R.; Ritchie, Ellen K.; Leibowitz, David; Demakos, Erin P.; Miller, Crystal; Siuty, James; Kleczko, Jill; Price, Leah; et al.
Abstract : We performed a multicenter, investigator initiated, phase I dose escalation study of the oral multi-kinase inhibitor lestaurtinib in patients with JAK2 V617F positive myelofibrosis, irrespective of baseline platelet count. A total of 34 patients were enrolled. Dose-limiting toxicities were observed in three patients overall, at the 100 mg ( n = 1) and 160 mg ( n = 2) twice-daily dose levels. The maximum tolerated dose was 140 mg twice daily. Gastrointestinal toxicity was the most common adverse event. Sixteen patients were evaluable for response at 12 weeks. Seven patients had clinical improvement by International Working Group – Myeloproliferative Neoplasms Research and Treatment criteria. Meaningful reductions in JAK2 V617F allele burden were not observed. To measure JAK2 inhibition in vivo, plasma from treated patients was assayed for its ability to inhibit phosphorylation of signal transducer and activator of transcription 5 (STAT5): doses lower than 140 mg had variable and incomplete inhibition. In this phase I study, although gastrointestinal adverse events were common, significant clinical activity with lestaurtinib was observed (ClinicalTrials.gov identifier: NCT00668421).